The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1213/01.ane.0000133916.10017.6d
|View full text |Cite
|
Sign up to set email alerts
|

The Laryngeal Mask Airway Unique??? versus the Soft Seal??? Laryngeal Mask: A Randomized, Crossover Study in Paralyzed, Anesthetized Patients

Abstract: We tested the hypothesis that ease of insertion, oropharyngeal leak pressure, fiberoptic position, ease of ventilation, and mucosal trauma are different for the Soft Seal laryngeal mask airway (SSLM) and the laryngeal mask airway Unique (LMA-U). Ninety paralyzed, anesthetized adult patients (ASA I-II; 18-80 yr old) were studied. Both devices were inserted into each patient in random order. Oropharyngeal leak pressure and fiberoptic position were determined during cuff inflation from 0-40 mL in 10-mL increments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
5
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 13 publications
9
42
5
3
Order By: Relevance
“…Our study found no correlation between the fibreoptic position and the functioning of these devices. This has also been demonstrated in other studies [13,14]. The absence of the aperture bars has not been found to influence the fibreoptic position; instead it may allow easier passage of instruments through the device into the respiratory tract and hence facilitate passage of a fibreoptic endoscope [5].…”
Section: Discussionsupporting
confidence: 62%
“…Our study found no correlation between the fibreoptic position and the functioning of these devices. This has also been demonstrated in other studies [13,14]. The absence of the aperture bars has not been found to influence the fibreoptic position; instead it may allow easier passage of instruments through the device into the respiratory tract and hence facilitate passage of a fibreoptic endoscope [5].…”
Section: Discussionsupporting
confidence: 62%
“…The thumb was used as a guide, squeezing the tube of the mask against the palate while introducing it with the other hand. In this case, the contamination of the surgical field was avoided and the insertion was successful in the first attempt, although it is considered more difficult than the cephalic approach 15,16 . The use of the "awake-asleep-awake" anesthetic technique with continuous infusion of remifentanil and propofol provided hemodynamic stability, complete awakening in a short time, and the patient remained cooperative for the aphasia test.…”
Section: Discussionmentioning
confidence: 95%
“…Usou-se o dedo polegar como guia, comprimindo o tubo da máscara laríngea contra o palato, enquanto realizava-se a sua progressão com a outra mão. Nesse caso, evitou-se a contaminação do campo cirúrgico e a inserção foi bem-sucedida na primeira tentativa, embora seja considerada mais difícil do que a abordagem cefálica 15,16 . O uso da técnica "dormindo-acordado-dormindo", com infusão contínua de remifentanil e propofol nesse caso, propor-…”
Section: Discussionunclassified
“…No prior data were available regarding success rates for insertion of either device. Brimacombe et al reported the first-time success rate for insertion of the Portex Soft Seal TM Laryngeal Mask to be 80% and that of the LMA Unique Ò to be 89% [17] (both examples …”
Section: Methodsmentioning
confidence: 99%